Association between obstetric and medical risk factors and stillbirths in a low‐income urban setting. Issue 2 (29th December 2020) - Gwako, George N.; Obimbo, Moses M.; Gichangi, Peter B.; Kinuthia, John; Gachuno, Onesmus W.; Were, Fredrick
Abstract: Objective: To evaluate the association between obstetric and medical risk factors and stillbirths in a Kenyan set‐up. Methods: A case‐control study was conducted in four hospitals between August 2018 and April 2019. Two hundred and fourteen women with stillbirths and 428 with live births at more than >28 weeks of gestation were enrolled. Data collection was via interviews and abstraction from medical records. Outcome variables were stillbirth and live birth; exposure variables were sociodemographic characteristics, and medical and obstetric factors. The two‐sample t test and χ 2 test were used to compare continuous and categorical variables respectively. The association between the exposure and outcome variable was done using logistic regression. A P value less than 0.05 was considered statistically significant. Results: Stillbirth was associated with pre‐eclampsia without severe features (odds ratio [OR] 9.1, 95% confidence interval [CI] 2.6–32.5), pre‐eclampsia with severe features (OR 7.4, 95% CI 2.4–22.8); eclampsia (OR 9.2, 95% CI 2.6–32.5), placenta previa (OR 8.6 95% CI 2.8–25.9), placental abruption (OR 6.9 95% CI 2.2–21.3), preterm delivery(OR 9.5, 95% CI 5.7–16), and gestational diabetes mellitus, (OR 11.5, 95% CI 2.5–52.6). Stillbirth was not associated with multiparity, anemia, and HIV. Conclusion: Proper antepartum care and surveillance to identify and manage medical and obstetric conditions with the potential to cause stillbirth are recommended. Synopsis: Stillbirth is associated with hypertensive disorders, gestational diabetes, and prepartum hemorrhage. Proper prepartum care and surveillance to identify and manage these conditions is recommended.